Systematic Literature Review: Students' Self-Regulated Learning at Different Levels of Education in Indonesia - Leana, Kunthy Ley; Saleh, Sitti Fithriani; Marup, M; Ilyas, Mutiara M. (Proceeding International Conference on Mathematics and Learning Research, 2024)
Self-regulated learning (SRL) is an important skill for students. Students who have SRL can regulate and control themselves in the learning process, especially when dealing with school assignments. The purpose of this study was to review the literature on students' SRL at different levels of education in Indonesia. This study is qualitative and uses the systematic literature review method. The data collection technique used in this study was a literature study and documentation sourced from articles using the keywords "self-regulated learning", "mathematics", and "students". Articles were screened using Publish or Perish software with Google Scholar, Crossref, and Semantic Scholar databases. A total of 2993 works of literature were screened and analyzed using Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) so that 9 articles were obtained representing each level of education. The study results showed differences in students' SRL levels at each level of education. Elementary school students have relatively low SRL. High school students have SRL levels varying between moderate and low.